The Impact of Debt Restructuring on Debt Maturity, Cost of Capital and Cash Holding of Non-Financial Institutions in Developing Countries: A Conceptual Framework - Alfawzan, Loulwah Suliman; Ab Razak, Nazrul Hisyam; Tunde, Matemilola Bolaji; Ashhari, Zariyawati Binti Mohd (Advances in Social Sciences Research Journal, 2023)
This paper delves into the integral role of debt restructuring in shaping the financial architecture of non-financial firms, particularly within developing nations. In volatile economic environments, understanding the nuances of debt restructuring becomes paramount for these entities. Key findings indicate that smaller non-financial enterprises, often constrained by financial limitations, rely on debt as a tool for operational continuity, with a marked preference for long-term maturity. The research further elucidates the broader repercussions of debt restructuring on a firm’s cost of capital. For nascent enterprises, immediate capital for new ventures is challenging to procure. Debt restructuring, especially with extended debt periods, emerges as a strategic fulcrum, enabling these firms to navigate fiscal challenges and capitalize on future growth prospects. The nexus between debt restructuring and a firm’s cash reserves is accentuated during economic downturns. Effective liquidity management becomes vital, as companies balance between expenditure and savings. The technological disparity between firms in developed versus developing nations further complicates this dynamic. While advanced entities harness cutting-edge technologies, their counterparts in developing regions grapple with outdated infrastructures and, at times, lax corporate governance. This study underscores that for many firms in developing nations, debt restructuring transcends its role as a mere financial tool, evolving into a critical lifeline that facilitates economic resilience and growth.